2018
DOI: 10.3349/ymj.2018.59.3.356
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Blood Pressure and Prevalence of Hypertension in Korean Adults Based on the 1998–2014 KNHANES

Abstract: PurposeTo investigate trends in blood pressure (BP) and hypertension prevalence in Korea.Materials and MethodsBased on the Korean National Health and Nutrition Examination Survey (KNHANES) I (1998), II (2001), III (2005), IV (2007–2009), V (2010–2012), and VI (2013–2014), 56077 participants (23974 men and 32103 women) were included.ResultsMean systolic BP (SBP) and diastolic BP (DBP) decreased in both sexes (male SBP: 128.1 to 120.2 mm Hg, male DBP: 82.0 to 78.5 mm Hg; female SBP: 125.7 to 116.0 mm Hg and fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 23 publications
1
16
1
1
Order By: Relevance
“…Khang et al reported that SBP and hypertension substantially decreased among Korean childhood 10‐19 years of age between 1998 and 2008 in the KNHANES, a change that could not be explained by concomitant secular changes in obesity, diet, health behaviors, and sociodemographic factors . In the KNHANES data, the age‐standardized prevalence of hypertension decreased significantly in both sexes in Korean adults . However, our study results were not consistent with US data and previous Korean data.…”
Section: Discussioncontrasting
confidence: 99%
“…Khang et al reported that SBP and hypertension substantially decreased among Korean childhood 10‐19 years of age between 1998 and 2008 in the KNHANES, a change that could not be explained by concomitant secular changes in obesity, diet, health behaviors, and sociodemographic factors . In the KNHANES data, the age‐standardized prevalence of hypertension decreased significantly in both sexes in Korean adults . However, our study results were not consistent with US data and previous Korean data.…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, the prevalence of hypertension in Korea increased from 19.8% in 1990 to approximately 28% since 1998 [ 39 ]. Similarly, the proportion of hypertension as an underlying cause of ESKD in Korea has increased from less than 10% in 1980s to 16.0% in 1992 and then remained at 16.0% to 21.4% [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The food-frequency questionnaire consisted of the type, amount, and frequency of foods or drinks consumed during the previous day and was conducted via face-to-face interviews. Data on food items were converted to units of nutrients using the Food Composition Table developed by the National Institute of Agricultural Sciences (7th revision) and the database of the Korean Health Industry Development Institute for instant foods and imported foods [20].…”
Section: Nutrition Assessmentmentioning
confidence: 99%